Continuum Damage Mechanics to Model Glulam Beams Reinforced with Glued-In Steel Cables - Rhodes, Aaron (Department of Civil Engineering, 2024)
This study aims to investigate the use of Continuum Damage Mechanics (CDM) for the computational modelling of timber, a material known for its high variability and anisotropy. Timber has not had a standard way of performing computational mechanics like that of steel and concrete, which has made engineers hesitant to design with the material. Many other concerns, including durability and fire resistance have also hindered its use in modern construction. However, the benefits of timber construction on the environment are well known, and therefore, there is a need for a reliable and accurate computational model for timber. This study utilizes CDM to model the fibrous portion of timber, similar to Fibre Reinforced Polymers (FRPs), in the hopes of encouraging engineers to build sustainable structures with timber as the main structural material. The material model is implemented in the software ABAQUS using a User-Defined Material UMAT written in Fortran coding. This UMAT allows for the simulation of the nonlinear behavior of timber under different loads and boundary conditions. To validate the model, experimental tests on glulam beams internally reinforced with steel cables were conducted. The beams had varying diameters of steel cables (3mm, 5mm and 8mm) to investigate the effect of the diameter of the cables on the strength of the beams. The results were compared to the results obtained from a similar setup in the ABAQUS/CAE software. The results show that the UMAT closely represents the failure, strength, and displacement readings of the control experimental tests. However, it was unable to accurately represent interactions between the reinforcing steels and timber. Despite the lack of accuracy in the interactions between the reinforcing steels and timber, this research concludes that the UMAT is accurate and suitable for solid timber and glulam beams. The UMAT can be used to model the fibrous portion of timber in a similar way to FRPs, and therefore, it will allow engineering predictions to be made with regards to the strength of SA pine timber. This will lead to more sustainable structures and more confidence in timber as a structural material. The model can be used to design and analyze members with more accurate predictions of the structural behavior of timber. Overall, this research aims to encourage a sustainable future by providing engineers with a reliable and accurate computational model for timber, which will lead to more widespread use of timber in construction. The use of CDM for timber modeling opens up new possibilities for sustainable and environmentally friendly construction. Further research in this field can lead to even more accurate and reliable models for timber, making it a viable alternative to traditional building materials.